Fixed Functional Distal Shoe Appliance for Bilateral Loss of Deciduous Molars - Chanchala, HP; Nagaratna, PJ; Rashmi, S; Godhi, Brinda S (Journal of Orofacial Research, 2014)
Pediatric dentistry aims at preserving the deciduous teeth till its normal time of exfoliation as it maintains the integrity of the dental arches. Premature loss of deciduous teeth might lead to a wide range of implications such as the mesial migration of the erupting permanent first molars as well as the supra eruption of the opposing dentition. In such cases the intra alveolar type of space maintainer is given however such an appliance may not fulfill all the needs. So, modification of these conventional designs will be required. This paper describes a new design for distal shoe appliance in cases of bilateral loss of primary first and second molars prior to the eruption of the permanent mandibular first molars.